Indonesia’s multi-track diplomacy: efforts to address the educational rights of undocumented Indonesian migrant workers’ children in East Malaysia - Asma Amin; Resky Ramadhan Antuli; Ismah Rustam; Anbar Zahirah; Salmiati; Wandi Abbas; Pindiaman Hulu (Otoritas : Jurnal Ilmu Pemerintahan, 2026)
The right to education for undocumented children of Indonesian migrant workers (IMWs) in East Malaysia remains inadequately protected due to administrative exclusion, legal uncertainty, geographic remoteness, and fragmented cross-border governance. This study analyzes how Indonesia’s multi-track diplomacy operates to protect the right to education for undocumented children of IMWs in East Malaysia.  This research employs a qualitative explanatory design based on semi-structured interviews supported by document analysis. Data were analyzed through thematic coding using NVivo, with the application of triangulation and participant verification to enhance credibility. Findings indicate that educational protection functions through coordination across four main Tracks. Tracks One provides policy authority, diplomatic legitimacy, schools, documentation facilitation, and scholarships. Tracks Two translates formal commitments into operational support, particularly regarding student repatriation and placement. Tracks Four maintains access in remote plantation areas through mentor teachers who fill teaching vacancies. Tracks Five strengthens the system through temporary teaching, training, and the production of policy-relevant knowledge. This study makes a theoretical contribution by expanding multi-track diplomacy beyond conflict resolution and demonstrating its value as an analytical lens for cross-border social governance. It further demonstrates that effective coordination depends on functional complementarity, negotiated interdependence, and adaptive responses to structural constraints.